The Realization Of Social Justice For The Poor Citizens According To Legal Philosophy - Naomi Jesica; Meta Nadia Winata; Lusi Septiyati (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
Pancasila is an ideology of Indonesia. One of the precepts of Pancasila is the principle of Social Justice for All Indonesians implies that all Indonesian people have the same position before the law. But nowdays, there have been many cases of injustice against the poor citizens. Therefore this research journal is about the realization of social justice for the underprivileged people in the philosophy of law, especially based on the theory named Critical Legal Studies.Keywords: Critical Legal Studies; Injustice; Poor Citizens